Pengaruh Likuiditas, Leverage, Aktivitas, dan Profitabilitas terhadap Nilai Perusahaan pada Sektor Barang Konsumsi yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2018 - Anju Galingging; Fery Xaverius Aritonang; Herlina Novita (Universitas Batanghari Jambi, 2020)
The purpose of this study is to determine and analyze the effect of Liquidity, Leverage, Activity, and Profitability on Firm Value in the Consumer Goods Sector Listed on the Indonesia Stock Exchange for the period 2015-2018. This study uses a quantitative method with a desciptive type. The population of this study is the Consumer Goods Sector that is listed on the Indonesia Stock Exchange for the 2015-2018 period, as many as 50 companies. Sampling using purposive sampling and obtained a research sample of 60 samples from 15 sectors of consumer goods multiplied by 4 years. This research method uses multiple linear regression. The coefficient test results obtained from the Adjusted R Square value are 3.7%, which means that the variation in the Firm Value variable described by the independent variable is 96.3%. The research results simultaneously show that liquidity, leverage, activity, and profitability have no effect on firm value. Meanwhile, partially it shows that liquidity, leverage, and profitability have no and insignificant effect on firm value, but for the activity variable has a significant effect on firm value.